Influence of uridine diphosphate-glucuronosyltransferases (1A9) polymorphisms on mycophenolic acid pharmacokinetics in patients with renal transplant. (15th October 2018) - Ciftci, H. S.; Demir, E.; Karadeniz, M. S.; Tefik, T.; Nane, I.; Oguz, F. S.; Aydin, F.; Turkmen, A.
Abstract: Background: There are differences in pharmacokinetic of mycophenolic acid among individuals. The UGT1A9 enzyme is of special interest since it is the main enzyme involved in the glucuronidation of MPA. Single nucleotide polymorphisms in the UGT1A9 gene may be responsible for individual differences in the pharmacokinetics of MPA. The aim of this study was to explain MPA pharmacokinetics in UGT1A9 1399 C > T polymorphisms in Turkish renal transplant patients. Patients and methods: One hundred and twenty-five living-donor transplant recipients and 100 healthy control subjects underwent UGT1A9 1399 C > T genotyping using polymerase chain reaction–restriction fragment length polymorphism. Concentrations of MPA were determined with Cloned Enzyme Donor Immunoassay (CEDIA). Besides that, all the patients were monitored for acute rejection and graft function during the study period. Results: The UGT1A9 1399 C > T CC, CT, and TT genotype frequencies among patients were, respectively, 68.0%, 23.2%, and 8.8%. The CC, CT, and TT genotype frequencies among controls were, respectively, 63.0%, 23.0%, and 14.0%. There was no significant difference between patients and controls ( p = .480, p = .999, p = .286, respectively). At first month, respectively, through blood concentrations of MPA were significantly higher in UGT1A9 1399 C > T TT carriers than in CT and CC carriers ( p = .046). The doses for these patients were lower at first month ( p = .021). Acute rejection episodes were not associated with the CC vs CT or TT genotypes ( p = .064). Conclusions: Our results demonstrated a correlation between the UGT1A9 1399 C > T polymorphism and MPA pharmacokinetics among renal transplant patients. Determination of UGT1A9 polymorphism may help to achieve target of MPA blood concentrations.